IMPLEMENTASI MULTIPLE INTELLIGENCE FOR TEACHING PADA LEMBAGA PENDIDIKAN ISLAM TERPADU DI KOTA SORONG PAPUA BARAT - Muhammad Adnan Firdaus (Pascasarjana IAIN Sorong, 2021)
This research examines the implementation of Multiple Intelligence for Teaching in Creating Excellent Schools at Integrated Islamic Education Institutions in Sorong city, West Papua. To clarify the direction of this research, the problems discussed in the research are, First, How is the application of multiple intelligence for teaching in creating excellent schools at the Integrated Islamic Education Institute in Sorong city, West Papua?; Second, how is the output of students with multiple intelligence for teaching in creating excellent schools at the Integrated Islamic Education Institute in Sorong city, West Papua?. This research is qualitative, namely research that goes directly to the location to obtain and collect data. Data were collected in the field using observation, interviews, and documentation techniques to discuss these problems. The primary data source is the Principals of the Integrated Islamic Education Institutions in Sorong City. Secondary data sources are various references and school documents. The data collected was processed through three stages: data reduction, presentation, and conclusion. Finally, testing the validity of the data is done by triangulation of techniques and data sources.